Oculomotor palsy and drowsiness due to post-thrombectomy subarachnoid haemorrhage falsely suggesting transtentorial herniation - Timothy Kleinig; Logesh Palanikumar; Joshua Mahadevan (BMJ Neurology Open)
Introduction Post-thrombectomy subarachnoid haemorrhage (SAH) can result in oculomotor palsy and drowsiness, which may falsely suggest transtentorial herniation.Case presentation We present a case of right oculomotor nerve palsy presenting after endovascular thrombectomy (EVT) for a right middle cerebral artery (MCA) stroke. The patient presented with a significant right MCA syndrome and a National Institutes of Health Stroke Scale (NIHSS) score of 10 with CT perfusion demonstrating a large penumbral lesion and a CT angiogram confirming a right MCA M1 occlusion. After thrombectomy, the patient developed a 9mm dilated non-reactive right pupil, and a new ipsilateral near-complete oculomotor nerve palsy. Repeat code stroke imaging demonstrated perimesencephalic SAH). The patient was managed expectantly and her conscious state and oculomotor palsy gradually resolved with an excellent neurological recovery.Conclusion This case underscores the potential for post-thrombectomy perimesencephalic SAH as a rare mimic of symptomatic intracranial haemorrhage with mass effect manifesting as sudden-onset oculomotor nerve palsy.